Evolution of work in industry 5.0 - Schmidt, Pedro Augusto Sorpresi; Sozzo, Bruna Thais Silva (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 41 No especial (2025): Ciência da Computação, 2025)
This study aims to analyze and highlight the fundamental concepts of Industry 5.0, exploring the main perspectives related to its implementation, the future of work, and the adaptation and coexistence between workers and machines. Based on this analysis, the study seeks to address the main uncertainties surrounding Industry 5.0, particularly regarding the technological impact on workers and the integration between humans and machines. Additionally, it discusses the essential points for adopting this new industrial paradigm, aiming to promote a more balanced, sustainable, and secure work environment, contributing to reducing uncertainties about the potential replacement of people by machines and the precarization of working conditions. Finally, it concludes that technological evolution is essential for improving the quality of human work, provided it is accompanied by adequate policies and responsible management, emphasizing the importance of a human-centered approach and professional training.